Acknowledging Bahasa Melayu with BFSU, China: gateway to international education: academic visitation by Benmg Foreign Studies University - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
APB Research and Publication Coordinator and Dr. Rozaimah Rashidin Head of the Center for Malay Studies. Also present were lecturers from the Department of Malay Studies.